2020
DOI: 10.1002/cbdv.202000786
|View full text |Cite
|
Sign up to set email alerts
|

Methoxy‐Substituted Hydroxychalcone Reduces Biofilm Production, Adhesion and Surface Motility of Acinetobacter baumannii by Inhibiting ompA Gene Expression

Abstract: An increasing lack of available therapeutic options against Acinetobacter baumannii urged researchers to seek alternative ways to fight this extremely resistant nosocomial pathogen. Targeting its virulence appears to be a promising strategy, as it offers considerably reduced selection of resistant mutants. In this study, we tested antibiofilm potential of four synthetic chalcone derivatives against A. baumannii. Compound that showed the greatest activity was selected for further evaluation of its antivirulence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 65 publications
(135 reference statements)
0
5
0
Order By: Relevance
“…In line with our results, Ušjak et al . [73] showed that A. baumannii cells after treatment with 2′-hydroxy-2-methoxychalcone, a secondary metabolite, showed a decline in mRNA levels of the bap and ompA genes at concentrations of 70 and 35 µg ml −1 , respectively. Their report further suggested that decreased expression of bap and ompA led to a decrease in surface motility and adherence-related virulence properties.…”
Section: Discussionmentioning
confidence: 99%
“…In line with our results, Ušjak et al . [73] showed that A. baumannii cells after treatment with 2′-hydroxy-2-methoxychalcone, a secondary metabolite, showed a decline in mRNA levels of the bap and ompA genes at concentrations of 70 and 35 µg ml −1 , respectively. Their report further suggested that decreased expression of bap and ompA led to a decrease in surface motility and adherence-related virulence properties.…”
Section: Discussionmentioning
confidence: 99%
“…According to the report of Selvaraj et al, the expression of csuA/B and bfmR is associated with the surface motility of A. baumannii (Selvaraj et al, 2020). Although the role of motility in A. baumannii virulence is not fully established, many studies have reported that motility contributes to increased virulence (Blaschke et al, 2021; Eijkelkamp et al, 2013; Usjak et al, 2021). Therefore, we further investigated the effect of auranofin on A. baumannii motility and found that auranofin significantly inhibited motility (Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…The bacterial inoculum is then added and incubated under appropriate bacterial growth conditions with bound ECM proteins for a short period of time until binding is complete (~1-4 h). Finally, the excess of unbound bacteria is washed off with PBS and quantification is performed either by staining the bacteria and following colorimetric or microscopic evaluation or by serial plating following the Triton X-100 mediated detachment ( Smani et al., 2012 ; de Oliveira et al., 2016 ; Ušjak et al., 2021 ).…”
Section: Anti-virulence Potential Of Novel Compoundsmentioning
confidence: 99%